Healing the Heart : Leaving Darkness for Light - Sharifah Nadirah; Muhammad Anas (IMAN PUBLICATION SDN BHD, 2022)
One of the things we struggle with is fulfilling the expectations we set upon ourselves. We race against time and compete with one another to achieve our dreams, only to find ourselves feeling frustrated when things don't go our way. Over time, the frustrations and despair harden the heart. Over time, we find it is hard to be kind to ourselves and accept our flaws. Because everyone else seem to be living their life perfectly. But isn't Allah the only One who is Perfect? Aren't His plans for us perfect? How do we make peace with this frustrated feeling in our heart? Healing The Heart invites us on a contemplative journey of seeking Allah and His Guidance. This guidance that is meant to lead us gently and kindly to His Light. And with this Light, we will embrace compassion and self-acceptance.